A Moving and Exhausting Cosmos: A Discussion on Entropy - Thomas Nail; Joel White (Technophany)
A discussion between Thomas Nail and Joel White on the philosophical status of entropy. The discussion explores Nail's kinetic materialism, movement, entropy and the notion of exhaustion.